Performance of electrochemical aptasensor as antigen test in clinical samples for early diagnosis of leptospirosis - Uraiwan Kositanont; Benchaporn Lertanantawong; Kanitha Patarakul; Sirinapa Sripinitchai; Charin Thawornkuno; Thanyarat Chaibun; Chahya Kreangkaiwal; Wassa Waiwinya; Chamras Promptmas; Chatchawan Srisawat (Scientific Reports)
Abstract Early diagnosis of leptospirosis is critical for timely treatment and effective disease management. This study evaluated the diagnostic performance of a novel electrochemical aptasensor targeting the electron transfer flavoprotein subunit beta (EtfB) of Leptospira interrogans in clinical samples collected during the acute phase of leptospirosis. The aptasensor assay was tested using plasma samples and compared to the microscopic agglutination test (MAT), the standard reference method. To assess diagnostic performance, aptasensor results were evaluated against leptospirosis status as determined by MAT. Receiver operating characteristic (ROC) analysis identified a 40% decrease in electrochemical signal relative to the blank as the optimal cut-off, yielding an area under the curve (AUC) of 0.93. The assay demonstrated a sensitivity of 100% and a specificity of 80%. For diagnostic concordance, aptasensor results were compared with those obtained from the reference quantitative PCR (qPCR) method. The aptasensor exhibited 100% positive agreement and 57.1% negative agreement with qPCR. Notably, in patients with high MAT titers, the aptasensor outperformed qPCR in detection rates (100% vs. 25%). These findings indicate that the aptasensor assay is a highly reliable and effective antigen-based diagnostic tool for early leptospirosis detection, making it suitable for both low- and high-prevalence settings.